(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Aim- To review comprehensive literature on Bhurjah (Betula utilis D. Don) w.s.r. to its therapeutic activity. Background- Bhurjah (Betula utilis D. Don) is a very ancient traditional medicine, commonly known as Bhojpatra in Hindi and Himalayan birch in English. Bark of Betula utilis was used in ancient times for writing Sanskrit literature and texts. Ancient sages used Bhojpatra to write down manuscripts and those literature remains unaffected by microbes, environmental and biological factors. From immemorial time Bhurjah has been used in Yagya karma by the sages. Material And Methods- The literature review was compiled from distinctive available Ayurvedic literatures and various published literature relevant to Bhurjah. Conclusion- Bhurjah widely used in Ayurvedic system of medicine in the treatment of various diseases like Kustha (various skin diseases), Karnashoola (otalgia), Visarpa (erysipelas), Medovishahara (anti-obesity and anti-toxic), Vranashodhana (wound purification) and Tridoshashamana (Vata, Pitta, Kapha alleviation). It has studied for various therapeutic activities like, anti-microbial activity, anti-oxidant activity, anti-inflammatory activity, mild anti hyperglycemic activity, anticancer activity, anti-HIV activity. An effort has been done to explore the evidence based pharmacological activities of Bhurjah.